Sensor fusion for creating a three-dimensional model for mobile robot navigation. (24th July 2019) - Hruboš, Marián; Nemec, Dušan; Janota, Aleš; Pirník, Rastislav; Bubeníková, Emília; Gregor, Michal; Juhásová, Bohuslava; Juhás, Martin
This article deals with the design of an automated system for creating a three-dimensional model of the environment with its texture. The method for creating a three-dimensional model of the environment is based on the use of a two-dimensional scanner for which the supporting hardware has been designed and constructed. The whole system extends the use of a two-dimensional scanner that is embedded in a robotic system. Supporting hardware rotates the scanner around the scan axis. This will create a three-dimensional model of the environment using a two-dimensional scanner. Thus, the resulting three-dimensional scan is formed by subsequent two-dimensional scans, each shifted with respect to the previous one. It was necessary to design the appropriate software for hardware management to control the movement of the engine, the scanner, and to process the measured data. The proposed system can be placed on various exploration robotic systems that map the space using the proposed method. Wheeled, band robotic systems or drones can be used to explore hard-to-reach environment.